Law of Intellectual Property - SAW, Cheng Lim (Institutional Knowledge at Singapore Management University, 2014)
This Reading Law in Singapore book seeks to convey to potential law students a basic idea of what the discipline as well as the study of law is about. The core subjects which are compulsory in both law schools at the National University of Singapore and Singapore Management University are identified and experts from either institution have been invited to present a ?taster? chapter on what it means to study that subject. Each chapter is written for the law school aspirant who may have little or no knowledge of the law. It is hoped that this book will be able to sketch an idea of what it is like to study law in Singapore. The core subjects that are covered in this book are Contract Law, Criminal Law, Tort Law, Legal Theory or Jurisprudence, Advocacy and Moots, Land Law, Comparative Legal Traditions, Public Law, Company Law, Equity and Trusts, and Evidence.